PEMBERDAYAAN IBU-IBU PKK MELALUI PENDIDIKAN UMKM DENDENG DAUN PEPAYA - Wiji Astika, Yulia; Sasmita Rusnaini; Ira Widyastuti; Tarjo; Syah Amin Albadry; Teta Wismar (Politeknik Negeri Sriwijaya, 2023)
The problem that occured in Dwi Karya Bakti Hamlet was that PKK activities and programs were not active in the village. The challenge undertaken by the service team was to reactivate the activities and programs that had been prepared by the PKK Dusun Dwi Karya Bakti. For this reason, the social service team approached the head of the committee and looked for problems and solutions to these problems. From these observations, the service team received information that the community, especially the member of PKK needed a facilitator or mentor to develop the PKK so that the PKK could be active again. The target of this activity focused on empowering the members of PKK in Dwi Karya Bakti. The aimed of carrying out this community service activity was to increase household income, entrepreneurial for the members of PKK, and improved the social life of the residents of Dwi Karyabakti. The methods used in this activity were educational methods and mentoring methods. Educational methods include training and mentoring methods included direct practice in making Dendeng Daun Pepaya. The implementation of the social service activities that have been carried out has a positive impact on the community, namely the members of PKK who were the targets of these service activities. The members of PKK Dwi Karya Bakti have started to have motivation to improve their abilities and creativity in developing UMKM.